Quadcopter aircraft using Arduino Mega: article / Noor Hadila Ismail - Ismail, Noor Hadila (2014)
The title of this project is Quadcopter Aircraft Using Arduino Mega. There are many previous researches about quadcopter aircraft however the difference this research from others is the microcontroller that used to control the movement of the quadcopter. Microcontroller is the brain of the device which contains a processor core, memory and programmable input/output peripherals. There are many type of microcontroller in the market nowadays for example is arduino mega. The arduino mega is a board based on the ATmega1280 which is programmed using Arduino programming language and the Arduino development environment. It used c++ language to programming the arduino mega. This project is developed from scratch by doing a lot of research on the project through many sources especially from internet in order to achieve the objective. Selecting the components is based on the cheapest and the important only because the objective of this project is to design the simple, easy and cheap quadcopter aircraft. Programming will be done after assembly all the components needed and troubleshoot the device if there is any problem occurs. Unlike helicopter, quadcopter have four propellers rotate by four brushless motors control by the microcontroller. The movement and speed of the quadcopter can be controlled by the keyboard or transmitter depends on the users. Each of the motor is supported by Electronic Speed Controller (ESC) due to the power hunger. The idea of this project is to build a quadcopter and test how the arduino mega programming functional as a microcontroller to the quadcopter aircraft.